English for Professional Training Classes: When the Online Classroom and the Work Field are in one Corporation - Ika Fitriani; Pusfika Rayuningtya (Pascasarjana Universitas Negeri Makassar, 2022)
Bridging background knowledge and present issues or demand, as well as preparing students for facing the future need to have pivotal positions during the teaching and learning process. Particularly in the context of teaching students who are working while pursuing higher study, the process of teaching and learning English for professional classes has its challenges both for teachers and students. EFL classrooms, then, should be able to bring contextual meaning through suitable materials, activities, and assessments. This present study is a retrospective study that elaborates on how an online professional English training class in STT STIKMA Malang was conducted based on the students’ work to match the students’ needs. It was found out that the use of work-based materials blended with the current issues is found to be effective to promote the students’ critical thinking during the teaching and learning process. The work-based activities assessments are also able to increase students’ online participation throughout the process of the language classroom. Furthermore, from the study, it was also found that students also give positive responses due they can link the English language learned in the class with the specific work that the students have.